Correlation between the Nutrition Alert Form (NAF) and the Mini Nutritional Assessment Short-Form (MNA-SF) in Hip Fracture Patients - Unhapipatpong, Chanita; Punsiha, Teppitugs; Sessumpun, Kittipong; Chupisanyarote, Kanokarn; Julanon, Narachai (Biomedical Sciences and Clinical Medicine, 2024)
Objective Malnutrition in hip fracture patients can lead to poorer outcomes. The Mini Nutritional Assessment Short-Form (MNA-SF) is a reliable tool for identifying malnutrition risk. This study aimed to assess the correlation between the Nutrition Alert Form (NAF) and MNA-SF, using either body mass index (BMI) or calf circumference (CC) scores, in adult inpatients with hip fractures. Additionally, the study sought to correlate NAF scores with other nutrition parameters and comorbidities. Methods A cross-sectional study was conducted at Khon Kaen Hospital, involving hip fracture patients. Spearman’s rank correlation coefficient (r) was utilized for analysis, with the NAF including patient-directed questions and either BMI (NAF-BMI) or total lymphocyte count (NAF-TLC) when BMI data were unavailable. Results A total of 152 patients were included in the analysis. The mean age was 68.0±16.7 years, with 31.6% being male. Mean body weight and BMI were 55.1±11.9 kg and 22.2±3.8 kg/m², respectively. MNA-SF (BMI) and MNA-SF (CC) identified 44.1% and 79.6% of patients, respectively, as at-risk for malnutrition, while NAF-BMI and NAF-TLC identified 27.6% and 40.1%, respectively. Moderate correlations were observed between NAF-BMI and MNA-SF (BMI) (r = - 0.57, p < 0.05) and MNA-SF (CC) (r= - 0.58, p < 0.05). NAF-BMI, NAF-TLC and MNA-SF (CC) were also moderately correlated with the Charlson Comorbidity Index. Conclusions NAF-BMI and NAF-TLC are both effective screening tools for identifying malnutrition risk in hospitalized hip fracture patients, demonstrating good correlation with MNA-SF as established nutrition screening tools.